Students' Perception of the Quality of Counseling Guidance Teacher Services - Eka Syahputri; Nurussakinah Daulay (Universitas Muhammadiyah Enrekang, 2024)
This study aims to identify students' perceptions of the quality of Guidance and Counseling (BK) teacher services at school, specifically at the Delisha Education Foundation. Students' perceptions of BK services encompass aspects of discipline, appearance, BK teachers' understanding of the guidance field, types of services provided, and BK teachers' skills in delivering services. The research employs a qualitative method with a phenomenological approach, involving 5 eleventh-grade students as research subjects. Data were collected through interviews and observations, then analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing/verification. The results of the study indicate that students have a positive view of the role of BK teachers. They perceive that BK teachers are able to provide emotional support and practical solutions effectively in helping them overcome personal, academic, and social problems. BK teachers are also considered to have good listening and understanding skills regarding students' issues and provide sufficient information about career options and educational paths after graduation. However, some students suggested that the availability of BK teachers' time should be increased for more optimal service. This study is expected to provide valuable insights into efforts to improve guidance and counseling services in schools and support the optimal development of students.